The "Jewish Chronicle" and Anglo-Jewry 1841- 1991 - Cesarani, David 1956-2015 (Cambridge Univ. Press, 1994)
No historian can understand the inner life of British Jews without looking at the social reports, the sports column, arts and cultural coverage and the advertising that the paper has carried. This book gives an insight into the working of a newspaper, the struggles between editors and directors and the boardroom politics. It is the story of a publishing adventure that became an institution and helped to shape the destiny of an entire community